Effect of exfoliation method on graphite oxide. A comparison between exfoliation by ball milling and sonication in different media. (November 2019) - Casallas-Caicedo, F M; Vera-López, E; Agarwal, A; Drozd, V; Durigin, A; Wang, C
Abstract: Graphene oxide and reduced graphene have been exfoliated from graphite oxide synthesized by Hummer's method. In order to establish a comparison, the exfoliation process was performed using two different methods, high energy ball milling and sonication. Each one was studied in two different media, organic solvent N-methyl 2 pyrrolidone and deionized water, obtaining four different products. The quality of the graphene and graphene oxides was studied using Raman spectroscopy. Structural characterization was performed using X-ray diffraction technique. The presence of oxygen-containing functional groups was determined by Fourier transform infrared spectra, while the morphology was investigated by scanning electron microscopy and energy-dispersive spectroscopy. The aim of this work is present a process to obtain graphene and graphene oxide of high quality at lower cost and better environmental conditions.